Surfactant-functionalised magnetic ferum oxide coupled with high performance liquid chromatography for the extraction of phenol - Beh, Shiuan Yih; Md Saleh, Noorashikin; Asman, Saliza (2021)
The usage of phenols in the marketplace has been increasing tremendously, which has raised concerns about their toxicity and potential effect as emerging pollutants. Phenol's structure has closely bonded phenyl and hydroxy groups, thereby making its functional characteristics closely similar to that of alcohol. As a result, phenol is used as a base compound for commercial home-based products. Hence, a simple and efficient procedure is required to determine the low concentration of phenols in environmental water samples. In this research, a method of combining magnetic nanoparticles (MNPs) with surfactant Sylgard 309 was developed to overcome the drawbacks in the classical extraction methods. In addition, this developed method improved the performance of extraction when MNPs and the surfactant Sylgard 309 were used separately, as reported in the previous research. This MNP–Sylgard 309 was synthesised by the coprecipitation method and attracts phenolic compounds in environmental water samples. Response surface methodology was used to study the parameters and responses in order to obtain an optimised condition using MNP–Sylgard 309. The parameters included the effect of pH, extraction time, and concentration of the analyte. Meanwhile, the responses measured were the peak area of the chromatogram and the percentage recovery. From this study, the results of the optimum conditions for extraction using MNP–Sylgard 309 were pH 7, extraction time of 20 min, and analyte concentration of 10.0 mg mL1. Under the optimized conditions, MNP–Sylgard 309 showed a low limit of detection of 0.665 mg mL1 and the limit of quantification was about 2.219 mg mL1. MNP–Sylgard 309 was successfully applied on environmental water samples such as lake and river water. High recovery (76.23%–110.23%) was obtained.